The Influence of Copper on the Microtexture of Fe-Si-Al Alloys for Non-Oriented Electrical Sheets - Steiner Petrovič, D.; Jenko, M.; Godec, M.; Vodopivec, F.; Jeram, M.; Prešern, V. (Metalurgija, 2007)
The effect of copper content in the range of 0,01 - 0,6 wt.% on the microtexture of some Fe-Si-Al non-oriented electrical sheets containing several impurity elements was investigated. The sheets were laboratory-manufactured and industrial samples of non-oriented electrical steels, decarburized and recrystallized, before the final annealing. Using the EBSD (electron backscatter diffraction) the microtexture was determined. It was found that the microtexture of the alloys containing more copper had fewer crystal grains with easy direction of magnetization in the sheet rolling plane. It was concluded that copper has a negative influence on the magnetic properties of soft-magnetic steel sheets.